2014
DOI: 10.5194/acp-14-9567-2014
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling temporal variability of near-ground atmospheric <sup>222</sup>Rn concentration over central Europe

Abstract: Abstract. Concentration of radon (222Rn) in the near-ground atmosphere has been measured quasi-continuously from January 2005 to December 2009 at two continental sites in Europe: Heidelberg (south-west Germany) and Krakow (southern Poland). The atmosphere was sampled at ca. 30 and 20 m above the local ground. Both stations were equipped with identical instruments. Regular observations of 222Rn were supplemented by measurements of surface fluxes of this gas in the Krakow urban area, using two different approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In general, during night, strength of the turbulent mixing decreases due to the removal of underlying heat sources. However, since the NBL was frequently lower than 180 m deep, the rapid nocturnal buildup of 222 Rn was not evident in our measurements at 180 m but usually observed at other sites, illustrating the accumulation of 222 Rn in the near‐ground atmosphere during the night [e.g., Zimnoch et al ., ]. Using trace gas measurements (e.g., CO and CO 2 ) on the TRN tower, Schmidt et al .…”
Section: Resultsmentioning
confidence: 99%
“…In general, during night, strength of the turbulent mixing decreases due to the removal of underlying heat sources. However, since the NBL was frequently lower than 180 m deep, the rapid nocturnal buildup of 222 Rn was not evident in our measurements at 180 m but usually observed at other sites, illustrating the accumulation of 222 Rn in the near‐ground atmosphere during the night [e.g., Zimnoch et al ., ]. Using trace gas measurements (e.g., CO and CO 2 ) on the TRN tower, Schmidt et al .…”
Section: Resultsmentioning
confidence: 99%
“…These parameters have a major infl uence on radon behaviour in the atmosphere. This was confi rmed by the measurements carried out by various authors who showed that radon time series are different in urban, suburban and rural environments [7,8].…”
mentioning
confidence: 68%
“…In addition, a harmonization of the experimental techniques applied for the measurements of atmospheric 222 Rn concentrations and 222 Rn fluxes is needed as suggested by the International Atomic Energy Agency [ International Atomic Energy Agency , ]. European long‐term 222 Rn monitoring stations, in agreement with the published literature, are presented in Figure with black labels [e.g., Chevillard et al ., ; Hatakka et al ., ; Taguchi et al ., ; Belviso et al ., ; Pitari et al ., ; Zimnoch et al ., ; Chambers et al ., ], and the lack of stations over the Mediterranean Basin is noticeable.…”
Section: Introductionmentioning
confidence: 98%
“…[]. The main aim of this collaboration is to extend the monitoring of atmospheric 222 Rn concentrations carried out in Europe by other research institutes [e.g., Levin et al ., ; Szegvary et al ., ; Belviso et al ., ; Zimnoch et al ., ] offering high‐quality data to the scientific community and working to fill the lack of harmonized 222 Rn data. Three stations: Gredos (GIC3), Delta de l'Ebre (DEC3), and Huelva (UHU), violet filled circles in Figure , are already operative and have been running continuously since December 2012, September 2013, and April 2014, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation